Predicting Men's Immediate Reactions to a Simulated Date's Sexual Rejection: The Effects of Hostile Masculinity, Impersonal Sex, and Hostile Perceptions of the Woman - Woerner, Jacqueline (Psychol Violence, 2018)
OBJECTIVE: Aggression is a common response to many types of social rejection. Men who respond aggressively to a woman's sexual rejection are likely to score high on risk factors associated with sexual aggression and to convince themselves that she is at fault. This study investigated how sexual dominance motivation and casual sex attitudes interact with “in the moment” hostile perceptions of the woman to predict the likelihood of an aggressive response. METHOD: Male participants (N = 77) completed an online survey including self-report measures of sexual dominance motivation and casual sex attitudes. In a separate session, participants completed a laboratory study in which they interacted with a female agent in a dating simulation, allowing them to make nonsexual choices, sexual choices that were accepted, and sexual choices that were rejected. Immediate responses to sexual rejection were categorized as aggressive (n = 25) or nonaggressive (n = 52). After the simulation ended, participants answered questions about their perceptions of the situation and the woman. Moderated multiple logistic regression analyses were used to test the hypotheses. RESULTS: The hypothesized interactions were found such that men with high scores on sexual dominance motivation and positive attitudes about casual sex had a greater probability of responding aggressively when they formed extremely hostile perceptions of the woman who rejected them. CONCLUSIONS: These findings provide insight into the processes by which men respond aggressively to women's refusals, and highlight the need for training that encourages benevolent attributions and nonviolent strategies to deal with sexual rejection.